Parametric Analysis of Concrete Solar Collectors. (June 2016) - O'Hegarty, Richard; Kinnane, Oliver; McCormack, Sarah
Abstract: Concrete solar collectors offer a type of solar collector with structural, aesthetic and economic advantages over current popular technologies. This study examines the influential parameters of concrete solar collectors. In addition to the external conditions, the performance of a concrete solar collector is influenced by the thermal properties of the concrete matrix, piping network and fluid. Geometric and fluid flow parameters also influence the performance of the concrete solar collector. A literature review of concrete solar collectors is conducted in order to define the benchmark parameters from which individual parameters are then compared. The numerical model consists of a 1D pipe flow network coupled with the heat transfer in a 3D concrete domain. This paper is concerned with the physical parameters that define the concrete solar collector, thus a constant surface temperature is used as the exposed surface boundary condition with all other surfaces being insulated. Results show that, of the parameters investigated, the pipe spacing, p s, concrete conductivity, k c, and the pipe embedment depth, d emb, are among those parameters which have greatest effect on the collector's performance. The optimum balance between these parameters is presented with respect to the thermal performance and discussed with reference to practical development issues.